Pengaruh Kemanfaatan NPWP, Pemahaman Wajib Pajak, Kualitas Pelayanan, dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak - Taurina, Tiara Putri; Nurdhiana, Nurdhiana; Triani, Triani (Jurnal Ilmiah Aset, 2020)
Taxpayer Compliance is a taxpayer who is aware of taxation, understands about the taxation rights and obligations and is expected to care about taxes, that is to, implement the taxation obligations properly and understands the taxation rights. The purpose of this research was to analyze the effect of the advantage of NPWP, taxpayer understanding, service quality, taxation penalty both partially and simultaneously on taxpayer compliance (empirical study on WP OP in KPP Pratama East Semarang). The population of this research were 46.261 and the samples used were 80. The sampling technique used was non-probability sampling. The analytical method used was the Data Quality Test (Validity Test and Reliability Test) and the Classic Assumption Test (Normality Test, Multicollinearity Test, Heterosedactivity Test). The analysis technique used multiple linear regression. Based on the result test partially (t test), the advantage of NPWP and taxation penalty had a positive effect on taxpayer compliance. Taxpayer understanding and service quality did not affect taxpayer compliance. The test results simultaneously (F test) showed the advantage of NPWP, taxpayer understanding, service quality, service penalty affected taxpayer compliance. The results of the coefficient of determination (Adjusted R2) showed that the advantage of NPWP, taxpayer understanding, service quality, service penalty were able to explain taxpayer compliance by 24% and the remaining 76% was explained by other variables.